Bezafibrate in men with lower extremity arterial disease: randomised controlled trial. Issue 7373 (16th November 2002) - Meade, Tom; Zuhrie, Riaz; Cook, Claire; Cooper, Jackie
Abstract : Objective: To assess the effect of bezafibrate on the risk of coronary heart disease and stroke in men with lower extremity arterial disease. Design: Double blind placebo controlled randomised trial. Setting: 85 general practices and nine hospital vascular clinics. Participants: 1568 men, mean age 68.2 years (range 35 to 92) at recruitment. Interventions: Bezafibrate 400 mg daily (783 men) or placebo (785 men). Main outcome measures: Combination of coronary heart disease and of stroke. All coronary events, fatal and non-fatal coronary events separately, and strokes alone (secondary end points). Results: Bezafibrate did not reduce the incidence of coronary heart disease and stroke. There were 150 and 160 events in the active and placebo groups respectively (relative risk 0.96, 95% confidence interval 0.76 to 1.21). There were 90 and 111 major coronary events in the active and placebo groups respectively (0.81, 0.60 to 1.08), of which 64 and 65 were fatal (0.95, 0.66 to 1.37) and 26 and 46 non-fatal (0.60, 0.36 to 0.99). Beneficial effects on non-fatal events were greatest in men aged <65 years at entry, in whom benefit was also seen for all coronary events (0.38, 0.20 to 0.72). There were no significant effects in older men. There were 60 strokes in those on active treatment and 49 in those on placebo (1.34, 0.80 to 2.01). There were 204 and 195 deaths from all causes in the two groups respectively (1.03, 0.83 to 1.26). Bezafibrate reduced the severity of intermittent claudication for up to three years. Conclusions: Bezafibrate has no effect on the incidence of coronary heart disease and of stroke combined but may reduce the incidence of non-fatal coronary events, particularly in those aged <65 years at entry, in whom all coronary events may also be reduced.